On-line acquisition of the output of a multi-channel analyzer (SMA 12/60) by means of an Elliott computer system - Carter, N. W. (1971)
The introduction of a multi-channel analyzer (Technicon SMA 12/60) into a laboratory, in which the outputs from single-channel, continuous flow analyzers (Technicon AA1) are acquired on-line to an Elliott 903 computer system presented an additional problem. One possible solution is discussed.